Update on clinical and immunological features of eosinophilic gastrointestinal diseases - Masterson, Joanne C. (2011)
PURPOSE OF REVIEW: Eosinophilic gastrointestinal diseases (EGIDs) are an increasingly common heterogeneous group of intestinal diseases. The purpose of this review is to present the latest developments in the care of patients with EGIDs and to summarize a growing literature defining the clinical features and mechanistic elements of eosinophils and their complex relationships with the gastrointestinal tract. RECENT FINDINGS: Recent studies continue to define what constitutes ‘normal’ and ‘abnormal’ numbers of eosinophils in the different sections of the gastrointestinal tract. Symptom complexes of EGIDs appear to be related primarily to the mucosal, as opposed to the muscular or serosal, forms of EGIDs. Dissection of the mucosal microenvironment is uncovering a complex array of cells, other than eosinophils, that likely contribute to the inflammatory response associated with EGIDs. Mechanistic studies have identified genetic perturbations (eotaxin-3, thymic stromal lymphopoietin, IL-13, and filaggrin) that may also contribute to the development of the most often encountered and well studied EGID, eosinophilic esophagitis. SUMMARY: Clinicians should remain aware of EGIDs as a diagnostic possibility for patients with common gastrointestinal symptoms. Additional research is needed to determine mechanistic processes leading to dysfunction associated with eosinophilic gastrointestinal inflammation.